Visual Collaboration Leader-Follower UAV-Formation for Indoor Exploration - Evangeliou, Nikolaos; Chaikalis, Dimitris; Tsoukalas, Athanasios; Tzes, Anthony (Frontiers in Robotics and AI, 2022)
UAVs operating in a leader-follower formation demand the knowledge of the relative pose between the collaborating members. This necessitates the RF-communication of this information which increases the communication latency and can easily result in lost data packets. In this work, rather than relying on this autopilot data exchange, a visual scheme using passive markers is presented. Each formation-member carries passive markers in a RhOct configuration. These markers are visually detected and the relative pose of the members is on-board determined, thus eliminating the need for RF-communication. A reference path is then evaluated for each follower that tracks the leader and maintains a constant distance between the formation-members. Experimental studies show a mean position detection error 5x5x10cm or less than 0.0031% of the available workspace (0.5 up to 5~m, 50.43 degrees by 38.75 degrees Field of View (FoV)). The efficiency of the suggested scheme against varying delays are examined in these studies, where it is shown that a delay up to 1.25 seconds can be tolerated for the follower to track the leader as long as the latter one remains within its FoV.